2023
DOI: 10.1002/pd.6302
|View full text |Cite
|
Sign up to set email alerts
|

Turner syndrome‐omphalocele association: Incidence, karyotype, phenotype and fetal outcome

Abstract: Objective Omphalocele is known to be associated with genetic anomalies like trisomy 13, 18 and Beckwith–Wiedemann syndrome, but not with Turner syndrome (TS). Our aim was to assess the incidence of omphalocele in fetuses with TS, the phenotype of this association with other anomalies, their karyotype, and the fetal outcomes. Method Retrospective multicenter study of fetuses with confirmed diagnosis of TS. Data were extracted from a detailed questionnaire sent to specialists in prenatal ultrasound. Results 680 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Besides that, a gradually apparent IUGR was also observed in the present case, which was characterized by the limited growth of both femur and humerus and the length of both long bones also presented a progressive growth retardation with gestation weeks. IUGR occurred in 25 cases as five literatures reported [6,7,8,12,14], among which total 21 cases reported the short femur and 4 cases reported IUGR without specific growth parameters indicating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, a gradually apparent IUGR was also observed in the present case, which was characterized by the limited growth of both femur and humerus and the length of both long bones also presented a progressive growth retardation with gestation weeks. IUGR occurred in 25 cases as five literatures reported [6,7,8,12,14], among which total 21 cases reported the short femur and 4 cases reported IUGR without specific growth parameters indicating.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal manifestation of edema in the hands, feet, and back is extremely rare. Only 3 cases with edema of feet in the fetal period was reported, two of them were presented as case report [11] reporting single ultrasonographic finding of dorsal foot edema in a female fetus; and the other one was presented in a retrospective study as associated findings with omphalocele [12]. There were no reports about the edema of hands detected by prenatal ultrasound so far although lymphedema is a common finding in infants with TS, who may have congenital lymphedema of the hands and feet.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that have analyzed fetuses with Turner syndrome and small omphalocele; the affected fetuses are at a high risk of miscarriage and intrauterine fetal death, especially with the karyotype 45,X, and if fetal hydrops is present. In a study on thirty-five fetuses with Turner syndrome and omphalocele, the detected cardiac anomalies were VSD/AVSD (5/35 cases), AVSD with coarctation of the aorta (1/35), hypoplastic left heart (3/35), coarctation of the aorta in one case, and pulmonary insufficiency in another case (at 25 weeks GA) [ 38 ]. In these cases with associated cardiac abnormalities, the pregnancy outcome was poor.…”
Section: Chromosomal Abnormalities and Syndromesmentioning
confidence: 99%
“…The impact of SCA screening is already evident in Australia, where a population‐based study has demonstrated a significant increase in the prenatal detection of SCAs, most notably 47,XXY, since the availability of NIPT 4 . In concert with these trends, we continue to integrate information about fetal sex chromosomes with prenatal ultrasound findings, including the assessment of atypical genitalia, 5 management of suspected X chromosome variants and monosomy X, 6 and expanding knowledge about the prenatal phenotype of 45,X 7 and 47,XXY 8 . Furthermore, Scarff et al.…”
mentioning
confidence: 99%